Evaluation of Renal Function After Percutaneous Nephrostomy in Obstructive Uropathy Due to Ureteropelvic Junction Obstruction (Bangladesh Journal of Urology, 2020)
Objective: The present prospective study was conducted to evaluate the renal function after percutaneous nephrostomy (PCN) in obstructive uropathy due to ureteropelvic junction obstruction. Patients of UPJ obstruction irrespective of sex upto 15 years of age and split renal function (SRF) of the affected kidney 10 ml/min/1.73 sq-meter at the 6 week of treatment. Four cases (10.5%) did not improve. The specific gravity of urine significantly increased from 1.009 at baseline to 1.019 after 6 weeks. The volume of urine at 2nd week was 338 ml/24hour which sharply increased to 363 ml/24 hours at week 4 and nearly 386 ml/24hours after 6 weeks of PCN (p < 0.001).Conclusion: Present study recommends that as the likelihood of recovery of a severely damaged kidney (SRF < 10%) with UPJO following PCN is fairly satisfactory; none of the children with poorly functioning kidney should undergo nephrectomy without subjecting them to a PCN trial.Bangladesh Journal of Urology, Vol. 17, No. 1, Jan 2014 p.36-41